PENDAMPINGAN MASYARAKAT DAN INTERVENSI GIZI MELALUI GERAKAN CEGAH STUNTING ITU PENTIING DI KOTA PALOPO SULAWESI SELATAN - Ningrum, Ratih Setia; Usrah, Ayyada; Saribulan, Saribulan; Yazid, Auliyah Baba; Zahra, Rafika; Lestari, Yuyun; Amalia, Dinda; Fadilla, Dian; Kurniawati, Nur; Amalia, Putri; Yasmine Alifah, Adela Putri; Khatimah, Khusnul; Anggreni, Cahya; Zulkifli, Naurah Ghina Aulia Halid; Aswad A, Muhammad Hajarul; Beddu, Rahmawati (Universitas Padjadjaran, 2025)
This study explores community empowerment and nutritional interventions to address stunting in Purangi Subdistrict, Sendana District, Palopo City, South Sulawesi, Indonesia. The primary objective is to enhance community capacity and improve the nutritional status of children under five years of age using the Asset-Based Community Development (ABCD) approach. This method leverages local assets, including community seed gardens and the transformation of land into nutrition gardens. Interventions included the provision of nutrition packages, caregiving, and the introduction of moringa leaf pudding as an innovative complementary food. Nutritional progress was monitored through the EPPBGM application provided by the local health center. Implemented from September to October 2024, the program yielded promising outcomes. Community assets were effectively mobilized through coordinated efforts with the local government and related agencies. As a result, one child successfully transitioned out of the stunting category. Nevertheless, further investigation is required to analyze the nutritional composition of the moringa pudding and evaluate its long-term effectiveness as a dietary intervention.Artikel ini membahas pendampingan dan intervensi gizi untuk mengatasi stunting di Kelurahan Purangi, Kecamatan Sendana, Kota Palopo, Sulawesi Selatan. Tujuannya adalah melakukan pemberdayaan masyarakat dan meningkatkan status gizi balita melalui pendekatan Asset-Based Community Development (ABCD) melalui pemanfaatan aset lokal seperti kebun bibit rakyat dan lahan kosong menjadi kebun gizi. Intervensi juga dilakukan dengan pemberian paket gizi dan perawatan, serta inovasi makanan pendamping berupa puding daun kelor. Pemantauan gizi dilakukan menggunakan aplikasi EPPBGM dari Puskesmas setempat. Kegiatan ini dilaksanakan pada September–Oktober 2024 dengan hasil yang positif. Aset yang dimiliki masyarakat setempat untuk memenuhi kebutuhan gizi, berhasil dimaksimalkan melalui koordinasi dengan pemerintah setempat dan beberapa dinas terkait. Setelah diberikan intervensi gizi, salah satu balita berhasil keluar dari kategori stunting. Namun, dibutuhkan kajian lanjutan mengenai kandungan gizi puding kelor dan efektivitasnya sebagai intervensi jangka panjang.